Applications of 3D printing in the teaching of human anatomy: An integrative review - Keila Danira Paim e Silva Cadete Tomás; Maíza Rodrigues Silva; Vanessa Namieh Garicoix; Lilian Navarro Wenceslau Giacometti; Victor Giovanni Ramos Cardoso; Josemar Santos de Matos; Braulio Henrique Magnani Branco; Lucas França Garcia; Audrei Pavanello; Karina Miura da Costa (Annals of 3D Printed Medicine)
This study consists of a review that explores the application of three-dimensional (3D) printing in the teaching of human anatomy. A search was conducted in the PubMed, Scopus, and Web of Science databases, using the terms ''3D Printing'', ''Health'', ''Education'', and ''Anatomy''. Articles published between 2019 and 2024 addressing the use of 3D printing for the production of anatomical models in the teaching of human anatomy were selected. The review included 15 articles, covering printed models from the circulatory, skeletal, nervous, and reproductive systems. 3D printing has been used to create detailed and customized anatomical models, offering three-dimensional visualization, anatomically precise details, and tactile feedback, assisting in memorizing anatomical structures. In addition, 3D printing can stimulate student engagement, resulting in better academic performance. Studies indicate that the novelty of the technology can increase student interest, leading to more effective learning. The customization of printed models allows for specific adaptations to the needs of students, improving the effectiveness of teaching. In conclusion, 3D printing has the potential to overcome the challenges of traditional anatomy teaching. As technology evolves, even more innovative applications in the field of anatomy education are likely to emerge. This study highlights the importance of integrating new technologies into the educational curriculum to improve student understanding and interest in subjects such as human anatomy.